Ibrutinib for the treatment of chronic lymphocytic leukemia. Issue 5 (4th May 2019) - Deodato, Marina; Frustaci, Anna Maria; Zamprogna, Giulia; Cairoli, Roberto; Montillo, Marco; Tedeschi, Alessandra
ABSTRACT: Introduction : Chemoimmunotherapy has improved outcomes in chronic lymphocytic leukemia, yet it is not curative, with very high relapse rates, and is associated with a significant risk of toxicities. Moreover, patients with higher-risk genetic abnormalities continue to experience poorer outcomes and lower survival. Recently, novel targeted therapies have been developed to increase efficacy and reduce toxicity. Areas covered : Ibrutinib is an oral irreversible inhibitor of Bruton's tyrosine kinase, a mediator of B-cell receptor signaling, which plays a vital role in various B-cell neoplasms. The drug has been approved for the treatment of several hematological malignancies, including chronic lymphocytic leukemia/small lymphocytic lymphoma, where large trials have shown outcomes never seen before even in high-risk patients. The safety profile appeared furthermore favorable, even in elderly and unfit patients. Expert opinion : Therapy with ibrutinib rarely provides MRD-negative complete remission; an indefinite maintenance is therefore needed, with the risk of developing adverse events (AE) or resistance resulting in treatment interruption or discontinuation. Novel, extremely promising, combination strategies, based on the association of ibrutinib with chemoimmunotherapy, anti-CD20 monoclonal antibody or other targeted agents, are currently being investigated, with the goal of achieving greater depth of remission, especially MRD-negativity, and removing the need for indefinite treatment.